Investigating the Readiness of Schools to Adopt AI Technologies: A Case Study Approach - Poniman Poniman; Windo Dicky Irawan (AI and Developmental Insights in Education, 2025)
Schools are increasingly expected to adopt artificial intelligence (AI) technologies, yet little is known about how prepared they are to integrate these tools into teaching and learning. This study examined the institutional, pedagogical, and infrastructural factors that shape school readiness for AI adoption. Using a qualitative multiple-case study design, data were collected from 21 participants across three schools through semi-structured interviews, classroom observations, and document analysis. Reflexive thematic analysis guided the analytic process. Three core themes emerged: leadership vision and structural readiness, teacher pedagogical readiness, and infrastructural and ethical preparedness. Although school leaders expressed strong enthusiasm for AI, formal policies and implementation mechanisms were limited. Teachers demonstrated varying levels of confidence and conceptual clarity regarding AI, and infrastructural constraints, alongside the absence of ethical governance structures, further hindered readiness. These findings show that AI adoption is influenced by the dynamic interaction of organizational culture, professional competence, and resource conditions. The study contributes a nuanced, contextually grounded understanding of AI readiness and offers guidance for developing strategic, ethical, and pedagogically meaningful approaches to AI integration in schools.